Strengthening of Intellectual Capital Dimension - Sarjana, Sri; Khayati, Nur; Warini, Lis; Praswiyati, Praswiyati (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2017)
The main objective of this research is to explore capabilities related to trust, self-efficacy, intellectual capital and job satisfaction at head-hunter companies in Indonesia. Development of human resources needs to be done through the strengthening of intellectual capital. Intellectual capital is needed head-hunter in improving company performance. The key to successful head-hunter companies if it has human resources that have added value, especially strong intellectual capital. Research sampling was conducted on 253 candidates who utilize head-hunter services an effort to develop themselves. Quantitative research was developed by utilizing structural equation modeling. Research model developed head-hunter companies that describes intellectual capital as research findings refers to previous model of research. This finding concludes that trust and self-efficacy have significant influence on intellectual capital. Another conclusion stated that intellectual capital has significant effect on job satisfaction. The concept states that intellectual capital can be integrated in global perspective as framework for developing an organization.